X-ray emission spectroscopy of proteinogenic amino acids at all relevant absorption edges - Meyer, Frank; Jeyachandran, Yekkoni Lakshmanan; Zharnikov, Michael (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2017)
Nonresonant N K, O K, C K, and S L2,3 X-ray emission spectra of the 20 most common proteinogenic amino acids in their solid zwitterionic form are reported. They represent a comprehensive database that can serve as a reliable basis for the X-ray absorption spectroscopy (XES) studies of peptides and proteins. At the most important N and O K edges, clear similarities and differences between the spectra of certain amino acids are observed and associated with the specific chemical structure of these molecules and their functional groups. Analysis of these spectra allows the generation of spectral fingerprints of the protonated amino group, the deprotonated carboxylic group, and, using a building block approach, the specific nitrogen- and oxygen-containing functional groups in the side chains of the amino acids. Some of these fingerprints are compared to the spectra of reference compounds with the respective functional groups; they exhibit reasonable similarity, underlining the validity of the spectral fingerprint approach. The C K and S L2,3 XES spectra are found to be specific for each amino acid, in accordance with the different local environments of the involved C and S atoms, respectively.